The Impact of Human Resource Development on Employee Productivity in North Central Timor Regency: The Mediating Role of Competence - Aziz, Syaefudin; Huda, Nurul; Mentu, Handrianus (Jurnal Manajemen dan Keuangan, 2024)
This study aims to analyze the direct and indirect effects of human resource (HR) development on work productivity, mediated by employee competence, in the context of organizations in North Central Timor Regency (TTU). This research employed an explanatory quantitative design, utilizing primary data collected through structured questionnaires administered to 349 employees in TTU Regency. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with the SmartPLS 4.0 software to test the mediation model. The findings show that HR development has a positive and significant direct effect on improving employee competence in TTU Regency. Employee competence directly and significantly enhances work productivity. The direct effect of HR development on work productivity in TTU Regency is positive but statistically insignificant. HR development exerts a positive and significant indirect effect on work productivity through employee competence as a mediating variable.